De la sainteté de Kaleb Ǝlla Aṣbǝḥa dans l’iconographie baroque portugaise - Faü, Jean-François Yazdani (Aethiopica, 2015)
The holiness of Kaleb Ǝlla Aṣbǝḥa in Portuguese baroque iconography reveals the trajectory of a major actor of the triumph of Christianity in the south of the Arabic peninsula. This Christian sovereign, who defeated the Jewish king of Ḥimyar, Ḏū Nuwās, in 525 CE, became one of the most popular figures of Catholic devotion in South America. Pedro Páez, a Spanish Jesuit who lived in Ethiopia at the beginning of the seventeenth century, mentions him in his História da Etiópia. Later, benefiting from the progressive recognition of the holiness of African saints, this iconographical subject was popularized by the Catholic Church, thus breaking with the figure of the other, that of Jew or Moor, that of the enemy. This pillar of the Ethiopian church, refashioned according to western criteria, was presented as a unifying element of the devotion of black people in Brazil and Portugal, among whom he acquired an increasing visibility. La sainteté de Kaleb Ǝlla Aṣbǝḥa dans l’iconographie baroque portugaise révèle le parcours d’une des figures du triomphe du christianisme dans le sud de la Péninsule arabique. Ce souverain chrétien, vainqueur en 525 du judaïsme ḥimyarite, représenté par Ḏū Nuwās, devînt une des figures les plus populaires de la dévotion catholique du Nouveau monde. Pedro Páez, un Jésuite espagnol ayant vécu en Éthiopie au début du XVIIème siècle, mentionne le souverain dans sa História da Etiópia. Puis, au-delà du cheminement de la reconnaissance sacrée de saints africains, ce thème iconographique fut popularisé par l’Église catholique, rompant ainsi avec la figure de l’autre, celle du Juif ou du Maure, celle de l’ennemi. Remodelé sur des critères occidentaux, ce pilier de l’Église éthiopienne fut présenté comme un des éléments fédérateurs de la religiosité noire d’Amérique lusophone, au sein de laquelle il tendait à prendre une visibilité de plus en plus importante.